'Poly phenolic phytoceutical loaded nano-bilosomes for enhanced caco-2 cell permeability and SARS-CoV 2 antiviral activity': in-vitro and insilico studies. (31st December 2023) - Zakaria, Mohamed Y.; Abd El-Halim, Shady M.; Beshay, Botros Y.; Zaki, Islam; Abourehab, Mohammed A.S
Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) predisposed to the emergence of worldwide catastrophe that impels the evolution of safe and effective therapeutic system. Polyphenols as resveratrol (RSV) exhibit a well evidenced antiviral activity. Unfortunately, like most phenolic nutraceuticals, RSV suffers from restrained solubility and massive degradation in GIT and liver which in turn prohibit its clinical use. Herein, PEGylated bilosomes (PBs) contain PEGylated edge activator along with the traditional components as (Span 60, cholesterol and bile salts) were proposed to boost both permeability and bioavailability of RSV. The investigation of the prominent effect of the diverse variables on the characteristics of the vesicles and picking of the optimum formula were conducted via construction of 2 3 factorial experiment. The appraisal of the formulae was conducted on the basis of entrapment efficiency percent (EE%), particle size (PS) and zeta potential (ZP). In addition, the spherical shaped optimal formula (F5) exhibited EE% of 86.1 ± 2.9%, PS of 228.9 ± 8.5 nm, and ZP of −39.8 ± 1.3 mV. The sorted optimum formula (F5) exhibited superior dissolution behaviors, and boosted Caco-2 cells cellular uptake by a round 4.7 folds relative to RSV dispersion. In addition, F5 demonstrated a complete in vitro suppression of SARS-CoV-2 at a concentration 0.48 μg/ml with 6.6 times enhancement in antiviral activity relative to RSV dispersion. The accomplished molecular modeling heavily provided proof for the possible interactions of resveratrol with the key residues of the SARS-CoV2 Mpro enzyme. Finally, F5 could be proposed as a promising oral panel of RSV for curation from SARS-CoV-2 infection.